Direct Pulp Capping With ProRoot MTA Alone and in Combination With Er:YAG Laser Irradiation: A Clinical Trial - Kermanshah, Hamid (J Lasers Med Sci, 2020)
Background: Due to the complications of root canal treatment, conservative modalities to preserve pulp vitality are favorable. Direct pulp capping (DPC) refers to the coverage of the pulp tissue exposed by a biocompatible agent that can improve the prognosis of the tooth by 44% to 95%. Some recent studies have reported more predictable results (a success rate of about 90%) for DPC with laser and regenerative materials such as mineral trioxide aggregate (MTA). This study aimed to clinically compare DPC with ProRoot MTA alone and in combination with Er:YAG (erbium-doped yttrium aluminium garnet) laser irradiation (2940 nm). Methods: This clinical trial was conducted on 26 patients with a mean age of 29 years (in the range of 17 to 46 years) who required DPC following pulp exposure during deep caries removal. The teeth were divided into two groups. In the control group, the teeth underwent DPC with ProRoot MTA while in the test group, the teeth were first irradiated with a 2940 nm Er:YAG laser and then underwent DPC with ProRoot MTA. The patients were recalled at one, 3 and 6 months for the follow-up (clinical and radiographic examinations). The data were analyzed using Fisher exact test. Results: The success rate was 75% in the laser group and 93% in the control group. The groups were not significantly different (P>0.05). Conclusion: No significant difference was found in terms of the success rate of DPC with ProRoot MTA alone and in combination with Er:YAG laser irradiation.